1993
DOI: 10.1515/jpme.1993.21.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal diagnosis and outcome in hydrops fetalis

Abstract: The records of 15 cases of hydrops fetalis consecutively delivered at our institution were reviewed to determine the accuracy of antenatal diagnosis and whether antenatal diagnostic techniques yielded information useful in predicting outcome. All 15 cases were detected antenatally, five were due to rhesus haemolytic disease and 10 were non-immune hydrops. All the infants required active resuscitation. Ten infants eventually died, two had immune hydrops fetalis and 8 non-immune hydrops. Seven infants had pleura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
1
8
2
Order By: Relevance
“…These findings are similar to the reports describing various antenatal and postnatal prognostic indicators in NIH [9,10,[18][19][20]58]. Gestational age was significantly associated with the mortality rate in our patients in contrast to Wafelman et al and Simpsom et al, respectively, although seven infants delivered at 5 30 weeks survived in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are similar to the reports describing various antenatal and postnatal prognostic indicators in NIH [9,10,[18][19][20]58]. Gestational age was significantly associated with the mortality rate in our patients in contrast to Wafelman et al and Simpsom et al, respectively, although seven infants delivered at 5 30 weeks survived in our study.…”
Section: Discussionsupporting
confidence: 91%
“…We investigated only live-born neonates with HF at our center because our point of interest was to examine the impact of medical progress on diagnostic spectrum and outcome during the postnatal period rather than during the prenatal period as has already been explored in other publications [4][5][6][7][8][9]. The prevalence of HF in this study was slightly lower than that reported for livebirths by Wafelman [10] but the precise occurrence of HF is difficult to determine due to fetal death or spontaneous resolution in utero.…”
Section: Discussionmentioning
confidence: 99%
“…However, the percentage of cases diagnosed prenatally in the present study (76%) is not significantly different from the 62% reported by Graves and Baskett [1] during 1975-1982 or from the 75% described by Brown [9] during the period 1975-1984. Neither did the gestational age at diagnosis by ultrasound in our study differ from that described in other studies [1,11,15,17]. The relatively low rate of prenatal diagnosis may be due to the fact that during the study period no prenatal sonographic screening program existed.…”
Section: Discussioncontrasting
confidence: 84%
“…Moreover, the small ones present a greater need for mechanical ventilation and more prolonged hospital stay, as well as increased intra-hospital mortality. 64,65 In the comparison of the Apgar score at the first and fifth minutes between the patients who received antenatal corticosteroids and those who did not, the newborns exposed to corticosteroid therapy presented a significantly greater average Apgar score at the first minute of life than those who were not. The higher Apgar scores for patients who received antenatal corticosteroids probably reflect the role that this class of medication plays in the cardiovascular and respiratory stabilization of premature neonates.…”
Section: Resultsmentioning
confidence: 99%